Evaluation of ionophore resistance in field isolates of Eimeria tenella from Jammu and Kashmir - KHURSHEED, AIMAN; YADAV, ANISH; YADAV, VIKAS; SOFI, OMER M; KUSHWAHA, ANAND; RAFIQI, SHAFIYA I; GODARA, RAJESH; SOOD, SHILPA; CHAKRABORTY, DIBYENDU; KATOCH, RAJESH (The Indian Journal of Animal Sciences, 2023)
The present study was conducted to evaluate resistance against ionophores (salinomycin and maduramicin) in four field isolates (F) of Eimeria tenella collected from four distantly located poultry farms from Union territory of Jammu and Kashmir. The purity of isolates was ascertained by COCCIMORPH and ITS-1 gene amplification for E. tenella. For the drug sensitivity trial, Cobb strain, day-old male broiler chicks were used. At the age of 10 days, the birds were transferred ad random in 13 groups to battery cage system. All birds, except non infected non-medicated control were infected with 105 sporulated oocysts each at two weeks. Prophylactic medication with ionophores commenced two days prior to infection in eight groups (two medicated groups for each of the four isolates). Another four groups served as infected and non-medicated control. Seven days post infection, all the surviving birds were sacrificed to study drug resistance by assessing the global index for individual ionophore compounds. The F-1 exhibited resistance against salinomycin and maduramicin whereas, the F-2 showed comparatively improved global index for both salinomycin and maduramicin thus indicating limited efficacy. The F-3 exhibited partial resistance against salinomycin and limited efficacy in case of maduaramicin, and the F-4 was observed to be resistant against salinomycin whereas partially resistant against maduramicin. The present study provides evidence of resistance against maduramicin and salinomycin in field isolates of E. tenella from Union Territory of Jammu and Kashmir which may aid in management of poultry coccidiosis.